Awareness and knowledge of glaucoma among hospital workers at the University of Benin Teaching Hospital, Benin City - Vivian Bose Osaguona; Omolabake Tolulope Edema (Sahel Medical Journal, 2014)
Background: Glaucoma is a disease of public health importance. We assessed the level of awareness and knowledge of glaucoma among workers at the University of Benin Teaching Hospital, Benin City, Edo State, Nigeria. Materials and Methods: This is cross-sectional study of hospital workers at the University of Benin Teaching Hospital, Benin City. Data on demographics, awareness and knowledge of glaucoma was gathered through structured self-administered questionnaires to a random sample of workers. Statistical analyses were performed with the Statistical Package for Social Sciences 16 (SPSS Inc. 2007. SPSS for Windows, Version 16.0. Chicago) software. Chi-square test was used to assess for any statistically significant difference in the social demographic factors such as age, gender, staff category, education, and duration of employment in the hospital and awareness of glaucoma. The level of knowledge among the staff categories was also compared using the Chi-square test. Statistical significance was taken as P < 0.05. Results: There were a total of 226 respondents. 93 (41.2%) were in the age group of 21-30 years. 111 (49.1%) were males. 168 (74.3%) were aware of glaucoma. Awareness of glaucoma was higher among the paramedical staff and among workers with a higher education (P < 0.001). The knowledge of glaucoma was good among 31% of those who were aware of glaucoma, fair in 31.5% and poor in 37.8%. Conclusions: There is a need to educate hospital workers on glaucoma in order to raise awareness and increase their level of knowledge such that blindness prevention from glaucoma may be possible from early diagnosis and prompt treatment in these workers, their relatives, and contacts.